IMPLEMENTATION OF THE JIGSAW METHOD IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS AT STATE ELEMENTARY SCHOOL 056635 PASIRAN AIR HITAM - Aniya Paramita (CV. Asry Persada Quality, 2025)
In the era of globalization that continues to develop, the world of education has become a topic that attracts the attention of many people, education is a capital that must be owned by everyone, therefore with a good educational background shows good quality. The purpose of this research is to determine the implementation of the jigsaw method in PAI learning at SD Negeri 056635 Pasiran Air Hitam. This research is a qualitative research with data collection techniques in the form of observation and interviews. As the results of the interview conducted, the implementation of the jigsaw method in PAI subjects is very effective with maximum results, where this method is very interesting, because it uses a fun method. The research results obtained are expected to be used as a basis for learning evaluation and as a reference for future research..